Lateral Radial Head Subluxation as a Complication Following Proximal Ulnar Osteotomy or Ostectomy in Eight Dogs - Williams, Heather; Arthurs, Gareth; Burton, Neil; Kulendra, Elvin; Radke, Heidi; Parsons, Kevin (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The aim of this study was to report the complication of lateral radial head subluxation following proximal ulnar osteotomy (PUOO) or proximal ulnar ostectomy (PUOE) in eight dogs.Materials and Methods Case records and diagnostic imaging of dogs developing lateral radial head subluxation following PUOO (n = 7) or PUOE (n = 2) were retrospectively reviewed. Information pertaining to clinical history, signalment, presenting condition, lameness grade, diagnostic imaging and initial surgery details, postoperative complications and their management were retrieved. Outcomes were established from subsequent clinical histories or telephone interviews with referring veterinarians. Comparison was made to a single-centre cohort without lateral radial head subluxation following PUOO or PUOE.Results Eight dogs (median age: 9.5 months [range: 6 months–6 years], median weight 7.7 kg [range: 5–28 kg]) were included. Six dogs had a PUOO performed; five dogs had unilateral surgery and one had bilateral surgery. Two dogs had unilateral PUOE surgery. Median time to diagnosis of lateral radial head subluxation following surgery was 6.5 weeks (range: 2–20 weeks). Five of the eight dogs had surgical revision of lateral radial head subluxation. Resolution of lateral radial head subluxation was achieved in four dogs, with three achieving acceptable to good mobility. One dog had poor postoperative mobility. A fifth dog remained lame after revision surgery failure. Three dogs did not have revision surgery; two underwent limb amputation and one dog remained lame as revision surgery was declined.Clinical Significance Lateral radial head subluxation is a potentially severe postoperative complication following PUOO or PUOE.
Keywords: proximal ulnar osteotomy; proximal ulnar ostectomy; radial head subluxation; complication